Monoclonal gammopathy of undetermined significance (MGUS) and smoldering (asymptomatic) multiple myeloma: IMWG consensus perspectives risk factors for progression and guidelines for monitoring and management - Kyle, R.A.; Durie, B.G.M.; Rajkumar, S.V.; Landgren, O.; Blade, J.; Merlini, G.; Kröger, N.; Einsele, H.; Vesole, D.H.; Dimopoulos, M.; San Miguel, J.; Avet-Loiseau, H.; et al. (Leukemia, 2010)
Monoclonal gammopathy of undetermined significance (MGUS) was identified in 3.2% of 21 463 residents of Olmsted County, Minnesota, 50 years of age or older. The risk of progression to multiple myeloma, Waldenstrom's macroglobulinemia, AL amyloidosis or a lymphoproliferative disorder is approximately 1% per year. Low-risk MGUS is characterized by having an M protein < 15 g/l, IgG type and a normal free light chain (FLC) ratio. Patients should be followed with serum protein electrophoresis at six months and, if stable, can be followed every 2-3 years or when symptoms suggestive of a plasma cell malignancy arise. Patients with intermediate and high-risk MGUS should be followed in 6 months and then annually for life. The risk of smoldering (asymptomatic) multiple myeloma (SMM) progressing to multiple myeloma or a related disorder is 10% per year for the first 5 years, 3% per year for the next 5 years and 1-2% per year for the next 10 years. Testing should be done 2-3 months after the initial recognition of SMM. If the results are stable, the patient should be followed every 4-6 months for 1 year and, if stable, every 6-12 months. © 2010 Macmillan Publishers Limited All rights reserved.
Keywords: International Myeloma Working Group; MGUS; monoclonal gammopathy of undetermined significance; Smoldering multiple myeloma